The influence of information technology on attention and concentration in sports performance: A literature review - Professor Zamira Madina; Tayyeba Shoaib (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The basic aim of this research study is to determine the influence of information technology on attention and concentration in sports performance. This research study is based on the literature review and some portions based on the numerical analysis. For this purpose, I used SPSS software and generated informative results related to the variables. Information technology is the main independent variable, attention, and concentration. Also, sports performance are present dependent variable. The descriptive statistic, the one-way ANOVA test analysis, and the regression analysis also explain the control chart related to them. Through a variety of mental training methods, including mindfulness exercises, imagery, and focusing techniques, athletes can improve their ability to pay attention and concentrate. Athletes frequently work with coaches and sports psychologists to develop these mental abilities and enhance their sporting performance by utilizing the power of concentrated attention. The overall result found that information technology positively and significantly influences attention and concentration in sports performance.